Pengaruh Penggunaan Model Pembelajaran Two Stay Two Stray Berbatu Media Dokar Saja Terhadap Hasil Belajar Aksara Jawa Siswa Kelas IV - Siti Dwi Andriyanti; Purwati Purwati; Galih Istiningsih (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of using the twostay twostray learning model withthe help of gig media on learning outcomes of Javanese script in fourth grade students ofGondangrejo State Elementary School, Windusari, Magelang.The design of this study used a Pre-experimental design with the One Group PretestPosttest Design research model. This research was conducted on fourth grade students ofGondangrejo State Elementary School Windusari Magelang. The research sample wastaken in total from the population with a sample of 20 students using a total samplingtechnique. The method used in collecting data in this study used the test method. Thevalidity test carried out in this study is construct validity and empirical validity. Thereliability test uses Cronbach's alpha which produces a reliability index of 0.837.Prerequisite test consists of normality test and homogeneity test. The normality test inthis study obtained a significance value of 0.25 > 0.05 where the data was declared normal.Hypothesis testing using parametric statistical techniques, namely the Paired sample ttest,The results of the hypothesis test are shown by the paired sample t test of Javanese scriptlearning outcomes with a value of7. 725> 0.05, which indicates that there is an effect ofusing the Two Stay' Two Stray Learning Model with the help of Dokar Media Only onJavanese Script Learning Outcomes. The results of this study prove that there is an effectof using the Two Stay' Two Stray' Learning Model with the help of Dokar Media Only' onthe Learning Outcomes of Javanese Script,